Comparative transcriptome analysis reveals key long noncoding RNAs for cadmium tolerance in Tibetan hull-less barley - Foysal, Md Rafat Al; Qiu, Cheng-Wei; Wu, Feibo (Frontiers in Plant Science, 2025)
Cadmium (Cd) is one of the most hazardous and persistent heavy metal pollutants globally. Long noncoding RNAs (lncRNAs) play a crucial role in regulating plant gene expression under various abiotic stress conditions. This study investigated the response of the lncRNA transcriptome in the roots of two contrasting Tibetan hull-less barley genotypes, X178 (Cd-tolerant) and X38 (Cd-sensitive), to Cd stress using RNA sequencing. A total of 8299 novel lncRNAs were identified, with 5166 unique target genes associated with 2571 unique lncRNAs. Among these, 1884 target genes were regulated by cis-acting lncRNAs, while 3428 were regulated by trans-acting lncRNAs. By analyzing differential expression profiles in the two genotypes under Cd stress, 26 lncRNAs and 150 mRNAs were identified as potentially linked to Cd tolerance. Functional enrichment analysis revealed that the target genes were significantly enriched in detoxification and stress response functions, including pathways related to phenylalanine, tyrosine, tryptophan, ABC transporters, and secondary metabolites. Additionally, 12 lncRNAs forming 18 lncRNA-mRNA pairs were identified as key regulators of Cd tolerance. The functional roles of these lncRNA-mRNA interactions suggest that they modulate proteins such as DJ-1, EDR, PHT, and ABC transporters, which may contribute to the Cd tolerance observed in genotype X178. High-throughput sequencing results were validated by qRT-PCR. These findings deepen our understanding of lncRNAs as critical regulators of Cd tolerance in plants, offering valuable insights into the molecular mechanisms underlying heavy metal stress responses in crops.